AI Trust Framework and Maturity Model: Improving Security, Ethics and Trust in AI - Michael Mylrea; Nikki Robinson (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The following article develops an AI Trust Framework and Maturity Model (AI-TFMM) to improve trust in AI technologies used by Autonomous Human Machine Teams Systems (A-HMT-S). The framework establishes a methodology to improve quantification of trust in AI technologies. Key areas of exploration include security, privacy, explainability, transparency and other requirements for AI technologies to be ethical in their development and application. A maturity model framework approach to measuring trust is applied to improve gaps in quantifying trust and associated metrics of evaluation. Finding the right balance between performance, governance and ethics also raises several critical questions on AI technology and trust. Research examines methods needed to develop an AI-TFMM and validates it against a popular AI technology (Chat GPT). OpenAI's GPT, which stands for